2016
DOI: 10.1039/c6dt00628k
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Zn2+ and Cu2+ to the membrane disrupting fragment of amylin

Abstract: Amylin, a small peptide co-secreted from pancreatic β-cells together with insulin, is one of the hallmarks of type II diabetes. In the course of this disease, it misfolds into small oligomers or into an aggregated β-sheet amyloid fiber. The misfolding mechanism is not yet well understood, but it is clear that metal ions such as zinc and copper play an important role in the process. In this work, the coordination chemistry of Zn(2+) and Cu(2+) with the membrane-disrupting part of amylin (amylin1-19) is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 49 publications
8
37
2
1
Order By: Relevance
“…The synthesis of some hIAPP PEG‐ylated peptide fragments that encompass the main metal‐ion binding site of His18 has allowed us to determine the affinity and speciation of different copper(II) complexes, thus mimicking the hIAPP behaviour. Accurate speciation has contributed to the assessment of Cu 2+ –IAPP binding and to the resolution of recent conflicting suggestions about the amino acid sequence involved in the metal‐ion interaction . Taken together, our data indicate the involvement of the residues that precede His18, thus favouring amino acid peptide deprotonation toward the N terminus.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of some hIAPP PEG‐ylated peptide fragments that encompass the main metal‐ion binding site of His18 has allowed us to determine the affinity and speciation of different copper(II) complexes, thus mimicking the hIAPP behaviour. Accurate speciation has contributed to the assessment of Cu 2+ –IAPP binding and to the resolution of recent conflicting suggestions about the amino acid sequence involved in the metal‐ion interaction . Taken together, our data indicate the involvement of the residues that precede His18, thus favouring amino acid peptide deprotonation toward the N terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Using more advanced EPR methods or specific site labeling would help on the elucidation of the structure for Cu(II)-hIAPP complexes. In addition, Rowińska-Żyrek [100] has researched the coordination of Cu(II) and Zn(II) to the monomeric form of the membrane disrupting fragment of the peptide, which compromises residues 1-19. With a 4N (1N im and 3N N- ), besides His18 being crucial, the coordination mode is forced towards the N-terminal as only one amide is available after His18.…”
Section: Coordination Of Cu and Zn To Amyloid-β α-Synuclein And Amylmentioning
confidence: 99%
“…3.B, left). For the membrane disrupting fragment, hIAPP(1-19), the N-terminal amine, together with the N im of His18 and 2 molecules of water coordinate zinc at physiological pH [100] (Fig. 3.B, right).…”
Section: Coordination Of Cu and Zn To Amyloid-β α-Synuclein And Amylmentioning
confidence: 99%
“…54) and to the three preceding amides at the N-terminal side of His18 (ref. 52) and at Lys1. 55 An opposite effect was observed for Al 3+ and Zn 2+ at the same concentration levels.…”
Section: Islet Amyloid Poly-peptide (Hiapp) Amylinmentioning
confidence: 95%
“…In general, it has been reported that Zn 2+ ion binds to amylin at the imidazole ring of His18 and the amine group of Lys1. 51,52 At low Zn 2+ concentrations (100 mM) and in the early stages of aggregation (40 min), Zn 2+ induces the formation of even larger Zn 2+ -amylin aggregates than those formed at high concentrations of Zn 2+ . During the nal stages of aggregation (when the amylin brils are formed), ber formation is inhibited at low concentrations of Zn 2+ and accelerated at higher concentrations.…”
Section: Islet Amyloid Poly-peptide (Hiapp) Amylinmentioning
confidence: 99%